Star worlds : freedom versus control in online gameworlds - Bainbridge, William Sims (Book collections on Project MUSE., 2017)
"Star Worlds explores the future-oriented universe of online virtual worlds connected with popular science fiction--specifically, with Star Wars and Star Trek--that have been inhabited for over a decade by computer gamers. The Star Wars and Star Trek franchises, both of which have shaped the dominant science fiction mythologies of the last half-century, offer profound conceptions of the tension between freedom and control in human economic, political, and social interactions. William Sims Bainbridge investigates the human and technological dynamics of four online virtual worlds based on these two very different traditions: the massively multiplayer online games Star Wars Galaxies; Star Wars: The Old Republic; Star Trek Online; and the Star Trek community in the non-game, user-created virtual environment, Second Life. The four "star worlds" explored in this book illustrate the dilemmas concerning the role of technology as liberator or oppressor in our postindustrial society, and represent computer simulations of future possibilities of human experience. Bainbridge considers the relationship between a real person and the role that person plays, the relationship of an individual to society, and the relationship of human beings to computing technology. In addition to collecting ethnographic and quantitative data about the social behavior of other players, he has immersed himself in each of these worlds, role-playing 14 avatars with different skills and goals to gain new insights into the variety of player experience from a personal perspective"--